Ab initio research of a metal-free C/N van der Waals bilayer heterostructure with graphdiyne and g-C3N4. (4th February 2019) - Xiao, Ye; Chen, Mengshi; Yang, Yibin; Zhang, Menglong; Huang, Le
Abstract: The structural, electronic, and optical properties of a mono-layered graphdiyne and g-C3 N4 van der Waals (vdW) heterostructure are investigated by first-principle calculations. The bandgap of the vdW bilayer directly forms a type-II heterostructure in which spatially separated active states favor the production of photon-generated carriers. Due to carrier transfer at interfaces, a proper internal electric field is formed, which inhibits the recombination of photon-generated electron−hole pairs. This effect is beneficial for solar energy conversion. We also find that graphdiyne could act as an inorganic photosensitizer, and that the optical absorption spectrum under visible light is broadened. The results could reveal mechanisms for improved energy conversion properties.